2005
DOI: 10.1242/jcs.02629
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis towards hyaluronan is dependent on CD44 expression and modulated by cell type variation in CD44-hyaluronan binding

Abstract: The accumulation of the extracellular matrix glycosaminoglycan hyaluronan by tumours and tumour-associated stroma promotes cancer cell invasion and metastasis. Using the Dunn chamber chemotaxis assay, we demonstrate for the first time that high molecular mass hyaluronan acts as a soluble chemoattractant promoting the directional migration of MDA-MB-468 and MDA-MB-231 breast cancer cells. Moreover, chemotaxis towards hyaluronan, but not foetal bovine serum, can be abrogated following treatment of the cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 67 publications
1
92
0
1
Order By: Relevance
“…In breast cancer cell lines, hyaluronan seems to play a chemoattractant role in the directional migration of malignant cells in a CD44 activity-dependent manner (Tzircotis et al, 2005). In vivo, it has been demonstrated that hyaluronan is required for zebrafish gastrulation movements (Bakkers et al, 2004) and we highlighted that both hyaluronan and CD44 are involved in muscle cell precursors migration during Xenopus laevis development (Ori et al, 2006).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In breast cancer cell lines, hyaluronan seems to play a chemoattractant role in the directional migration of malignant cells in a CD44 activity-dependent manner (Tzircotis et al, 2005). In vivo, it has been demonstrated that hyaluronan is required for zebrafish gastrulation movements (Bakkers et al, 2004) and we highlighted that both hyaluronan and CD44 are involved in muscle cell precursors migration during Xenopus laevis development (Ori et al, 2006).…”
Section: Introductionmentioning
confidence: 78%
“…These findings suggest that the formation of hyaluronan-versican complexes may help to facilitate cranial NCC migration. Hyaluronan can promote cell locomotion also by interacting with cell membrane receptors, which modulate cell adhesion and trigger intracellular signaling (Bourguignon et al, 1997;Banerji et al, 1999;Tzircotis et al, 2005). The finding that CD44 down-regulated embryos exhibit an NCC migration delayed phenotype, similar to that observed in embryos depleted of both Has1 and Has2, suggests that CD44 could mediate the hyaluronan instructive effect that initiates signaling pathways and thus promotes NCC movements.…”
Section: Discussionmentioning
confidence: 93%
“…Chemotaxis was measured by direct observation and recording of cell behaviour in stable concentration gradients using Dunn chemotaxis chambers (Hawksley Technology, Lancing, UK) as described previously (Zicha et al, 1991;Allen et al, 1998;Tzircotis et al, 2005). Briefly, glass coverslips were coated with 1 mg/ml laminin (BD Biosciences, Cowley, UK) in PBS for 1 h at room temperature, washed twice with DMEM and then seeded with 5 Â 10 4 cells per coverslip.…”
Section: Chemotaxis Assaysmentioning
confidence: 99%
“…First, expression of CD44 by the tumour cells can increase the interaction with endothelial cells and transmigration across an endothelial monolayer (Fujisaki et al, 1999;Mine et al, 2003;Draffin et al, 2004;Ratliff, 2005). Second, in a wide variety of systems, increased CD44 expression has been shown to correlate strongly with increased invasive potential of tumour cells Jothy, 1999, 2001;Dingemans et al, 2002;Kobayashi et al, 2002;Bourguignon et al, 2003;Xu and Yu, 2003;Kim et al, 2004;Miletti-Gonzalez et al, 2005) and in particular, increasing evidence points to an important role for CD44 in mediating directional cell migration (Alstergren et al, 2004;Avigdor et al, 2004;Zhu et al, 2004Zhu et al, , 2005Miletti-Gonzalez et al, 2005;Tzircotis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Very localised stimuli at the cell surface often initiate intracellular signals and mechanical responses that are crucial in a number of cell processes such as chemotaxis and focal adhesion assembly. For example, HA can be an important chemoattractant molecule controlling the invasion of cancer cells [81]. Oliferenko et al have shown that the local application of an HA microgradient to glioblastoma cells induces major lamellipodia outgrowth via a rac-1-dependent signalling pathway [82].…”
Section: Perspectives: Induction Of Cellular Processes Through Afm-bamentioning
confidence: 99%